Identifying fit issues for the one-size-fits-all hospital patient gown: an anthropometric approach - Jankovska, Daniela, author; Park, Juyeon, advisor; Ruoh-Nan, Yan, committee member; Greene, David, committee member (Colorado State University. Libraries, 2015)
The purpose of this study was to identify fit issues associated with the hospital patient gown in order to facilitate a better fit and comfort of the hospital patient gown to as many potential patients as possible. To address the research questions, this study adopted a multi-dimensional fit and comfort evaluation protocol that consisted of a survey, 3D body scanning, scenario activities, and exit interview. Eighty-five participants (47 males and 38 females) participated in this study. The exploration of the fit and comfort of the hospital patient gown across gender, diverse age, and different BMI categories revealed three major issue that must be taken into consideration in order to achieve an the best fit and size for the hospital patient gown: (a) consideration of sensory clothing preferences and hospital patient gown design preferences, (b) 3D body measurements and (c) accommodation to common daily activities such as, walking, lying, bending, reaching up and sitting during hospitalization. Three-dimensional body scanning data identified the following anthropometric body landmarks that caused fit problems: neckline, shoulders, sleeves and armholes, bust/chest, abdomen and stomach, hips and knee circumference. The findings of the study suggest that there are major fit issues with the conventional hospital patient gown, which must be adequately addressed to provide its wearers with acceptable satisfaction with the fit of the gown.
Keywords: anthropometrics; fit; hospital patient gown; comfort; 3D body scanning; functional ease